2013
DOI: 10.1124/mol.112.083493
|View full text |Cite
|
Sign up to set email alerts
|

Phosphodiesterase 4 Inhibitors Augment the Ability of Formoterol to Enhance Glucocorticoid-Dependent Gene Transcription in Human Airway Epithelial Cells: A Novel Mechanism for the Clinical Efficacy of Roflumilast in Severe Chronic Obstructive Pulmonary Disease

Abstract: Post-hoc analysis of two phase III clinical studies found that the phosphodiesterase 4 (PDE4) inhibitor, roflumilast, reduced exacerbation frequency in patients with severe chronic obstructive pulmonary disease (COPD) who were taking inhaled corticosteroids (ICS) concomitantly, whereas patients not taking ICS derived no such benefit. In contrast, in two different trials also performed in patients with severe COPD, roflumilast reduced exacerbation rates in the absence of ICS, indicating that PDE4 inhibition alo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
63
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(67 citation statements)
references
References 40 publications
4
63
0
Order By: Relevance
“…In support of this, Moodley et al. (2013) have shown that combined roflumilast and FP treatment enhanced GRE‐dependent reporter activity and several GRE responsive anti‐inflammatory genes. Further studies are required to investigate the potential mechanism responsible for steroid sparing effects of CHF6001.…”
Section: Discussionmentioning
confidence: 99%
“…In support of this, Moodley et al. (2013) have shown that combined roflumilast and FP treatment enhanced GRE‐dependent reporter activity and several GRE responsive anti‐inflammatory genes. Further studies are required to investigate the potential mechanism responsible for steroid sparing effects of CHF6001.…”
Section: Discussionmentioning
confidence: 99%
“…Via a GRE-dependent molecular mechanism, roflumilast interacted with formoterol in a positive manner to enhance glucocorticoid-dependent transcription of anti-inflammatory genes, including as GILZ and RGS2 (36). Although the gene for MKP-1 (DUSP1) was not examined in the study, our data concur with those from the Giembycz group as they support the concept that "these drugs together may impart clinical benefit beyond that achievable by an ICS alone, a PDE4 inhibitor alone, or an ICS/LABA combination therapy" (36).…”
Section: Discussionmentioning
confidence: 99%
“…Via a GRE-dependent molecular mechanism, roflumilast interacted with formoterol in a positive manner to enhance glucocorticoid-dependent transcription of anti-inflammatory genes, including as GILZ and RGS2 (36). Although the gene for MKP-1 (DUSP1) was not examined in the study, our data concur with those from the Giembycz group as they support the concept that "these drugs together may impart clinical benefit beyond that achievable by an ICS alone, a PDE4 inhibitor alone, or an ICS/LABA combination therapy" (36). Although our in vitro experimental model of airway inflammation doesn't fully encapsulate the complexity of COPD, these studies, taken together, provide a molecular mechanism that may explain the benefits of adding roflumilast as an "addon" therapy in severe COPD, where patients are likely taking LABA and inhaled corticosteroids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adding roflumilast to indacaterol has shown an enhanced antifibrotic effect by inhibiting mediator release from fibroblasts and myofibroblasts. Activation of PKA is the mechanism underlying the additive effect between PDE4 inhibitor and long-acting beta-adrenoceptor agonists (LABAs) (33,34). However, the translation from a scientific basis to a clinical meaning is yet to be proven.…”
Section: Synergistic Effect Of Roflumilast and Other Antiinflammatorymentioning
confidence: 99%